Objective estimation of tropical cyclone wind structure from infrared satellite data - Mueller, Kimberly J., author; Vonder Haar, Thomas H., author; Cooperative Institute for Research in the Atmosphere (Fort Collins, Colo.), publisher (Colorado State University. Libraries, 2004)
Given the destructive nature of tropical cyclones, it is extremely important to provide quality estimates of intensity, as well as wind structure. The Dvorak technique, and an automated version, the Objective Dvorak Technique (ODT) use a method of identifying cloud characteristics from satellite images (visible and infrared), to provide estimates of current storm intensity. However, these IR techniques provide no information on the extent or location of damaging winds. Estimates of wind structure via alternate methods have significant disadvantages. Gathering data using aircraft is expensive; therefore storms are flown only if they are an immediate threat to the U.S. AMSU algorithms for estimating wind structure have proven successful, however the instruments fly aboard polar-orbiting satellites, which only pass over the tropics twice a day, and are not contiguous at or near the equator. It is apparent that an alternate method of estimating wind structure is necessary; one in which data coverage is continuous. While IR data has historically been used to estimate intensity, the goal of this research is to extend the use of IR data to estimate wind structure. Theoretically, there should be a solid relationship between deep convection and the extent of damaging winds. The database for this work includes aircraft reconnaissance data from 91 Atlantic and E. Pacific storms flown during the 1995-2003 seasons as ground truth, in combination with GOES IR imagery, and storm best track information. Using multiple linear regression techniques, with predictors derived from the IR data, a radius of maximum wind can be estimated, as well as, more accurately, the symmetric tangential winds at a radius of 200 km (size parameter). These estimated parameters are then fit to a modified combined Rankine vortex model to reconstruct the entire symmetric wind field. Given the storm motion vector, and researched relationships between storm motion and wind asymmetries, the asymmetric part of the wind field can be calculated and added to the symmetric part to provide an estimation of the entire tropical cyclone wind field.
Keywords: Cyclones -- Tropics; Satellite meteorology; Winds